(untitled) (Sains Humanika, 2025)
The trend of depression among university students is at a worrying level. Proactive steps must be taken seriously to curb this issue before students resort to non-suicidal self-injury or develop suicide ideation. Therefore, this study aims to examine the influence of personality traits and perfectionism on depression among undergraduate students. Specifically, this study also examines the influence of five personality dimensions (Openness to experience, Conscientiousness, Extraversion, Agreeableness and Neuroticism) on depression, as well as the influence of perfectionism on depression among university students. A convenience sampling method was employed which involving 106 undergraduate students from a university in Malaysia. Standardized instruments used to collect the data were the Big-Five Inventory (BFI), Frost’s Multidimensional Perfectionism Scale (FMPS) and Beck’s Depression Inventory (BDI). The data were analyzed using descriptive statistics and multiple regression analysis. The findings revealed that respondents demonstrated moderate levels across all personality dimensions, a high level of perfectionism, and a low level of depression. Additionally, the results indicated that Openness to experience, Agreeableness and Neuroticism significantly influenced depression. Perfectionism was also found to influence depressive symptoms among university students. Implications, recommendations and study limitations are further discussed.